2016
DOI: 10.1016/j.jpainsymman.2016.10.252
|View full text |Cite
|
Sign up to set email alerts
|

P194 The Utility of Herbal Medicine Yokukansan in Palliative Medicine

Abstract: Background: Methadone is an effective long acting opioid analgesic used to manage nociceptive and neuropathic pain. Its unique lipophilic properties, absence of active metabolites and high volume of distribution allows for delivery routes that are unique and innovative enabling patients uninterrupted and effective pain control at the end of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Hence, Yokukansan, which performs a serotonin-releasing action [ 13 , 14 ], may prevent depression in smokers. Additionally, it removes excessive glutamic acid, thereby reducing frustration, agitation, and aggressiveness [ 5 8 , 11 , 12 ]. A case study that used the Profile of Mood States (POMS) instrument reported that the use of Yokukansan for four weeks in five patients during the SC therapy tended to reduce anxiety, nervousness, and depression relative to pre-treatment levels [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, Yokukansan, which performs a serotonin-releasing action [ 13 , 14 ], may prevent depression in smokers. Additionally, it removes excessive glutamic acid, thereby reducing frustration, agitation, and aggressiveness [ 5 8 , 11 , 12 ]. A case study that used the Profile of Mood States (POMS) instrument reported that the use of Yokukansan for four weeks in five patients during the SC therapy tended to reduce anxiety, nervousness, and depression relative to pre-treatment levels [ 19 ].…”
Section: Introductionmentioning
confidence: 99%